Characterization of a microDiamond detector in high-dose-per-pulse electron beams for intra operative radiation therapy. Issue 8 (December 2015) - Di Venanzio, C.; Marinelli, Marco; Tonnetti, A.; Verona-Rinati, G.; Falco, M.D.; Pimpinella, M.; Ciccotelli, A.; De Stefano, S.; Felici, G.; Marangoni, F.
Abstract: Purpose: To characterize a synthetic diamond dosimeter (PTW Freiburg microDiamond 60019) in high dose-per-pulse electron beams produced by an Intra Operative Radiation Therapy (IORT) dedicated accelerator. Methods: The dosimetric properties of the microDiamond were assessed under 6, 8 and 9 MeV electron beams by a NOVAC11 mobile accelerator (Sordina IORT Technologies S.p.A.). The characterization was carried out with dose-per-pulse ranging from 26 to 105 mGy per pulse. The microDiamond performance was compared with an Advanced Markus ionization chamber and a PTW silicon diode E in terms of dose linearity, percentage depth dose (PDD) curves, beam profiles and output factors. Results: A good linearity of the microDiamond response was verified in the dose range from 0.2 Gy to 28 Gy. A sensitivity of 1.29 nC/Gy was measured under IORT electron beams, resulting within 1% with respect to the one obtained in reference condition under 60 Co gamma irradiation. PDD measurements were found in agreement with the ones by the reference dosimeters, with differences in R50 values below 0.3 mm. Profile measurements evidenced a high spatial resolution of the microDiamond, slightly worse than the one of the silicon diode. The penumbra widths measured by the microDiamond resulted approximately 0.5 mm larger than the ones by the Silicon diode. Output factors measured by the microDiamond were found within 2% with those obtained by the Advanced Markus down to 3 cm diameter field sizes. Conclusions: The microDiamond dosimeter was demonstrated to be suitable for precise dosimetry in IORT applications under high dose-per-pulse conditions. Highlights: A PTW microDiamond was investigated in high dose-per-pulse IORT electron beams. The microDiamond response exhibits no dose rate dependence up to about 60 mGy/min. The microDiamond response does not require any correction factor to be applied. A slight over-response of the silicon diode was observed at high dose per pulse.